EFL UNDERGRADUATE STUDENTS’ PERSPECTIVE ON USING AI-BASED CHATGPT IN ACADEMIC WRITING - Nisa Artiana; Ria Fakhrurriana (Language and Education Journal, 2024)
This study aims to explore the perspectives of English as a Foreign Language (EFL) Undergraduate Program students on the use of Artificial Intelligence (AI)-based ChatGPT in academic writing. This study uses a qualitative approach to understand students' views and experiences regarding the use of ChatGPT in the context of their academic writing. This study involved participants consisting of undergraduate EFL students who used ChatGPT in their writing assignments. Data was collected through in[1]depth interviews and analysis of academic writing documents produced by students. It is hoped that the results of this study will provide better insight into how undergraduate EFL students view the use of ChatGPT in academic writing, as well as the advantages and challenges they face in using this tool